Hubungan Pengetahuan Remaja Putri dengan Tindakan Personal Hygiene Saat Menstruasi di SMP Negeri 1 Pematangsiantar Tahun 2023 - Sri Ninta; Sri Rezeki; Amelia Erawaty Siregar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Menstruation is the discharge of blood from the genitals. During menstruation, the blood vessels in the uterus are very easily infected. In areas that are hot enough to make the body sweat, this sweat increases the body's moisture levels, especially in the closed and folded sexual and reproductive organs. The aim of the research is to determine the relationship between knowledge of young women and personal hygiene practices during menstruation at SMP Negeri 1 Pematangsiantar in 2023.The type of research carried out was Descriptive Analytical with a cross sectional approach, the population in the study was 35 people using Total Sampling. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi squareThe research results showed that the majority had sufficient knowledge with poor personal hygiene, 11 (31.3%) respondents with Chi square 0.001. the majority had poor attitudes with poor personal hygiene as many as 10 (28.5%) respondents with a Chi square of 0.000.The conclusion is that there is a relationship between knowledge and attitudes of young women towards personal hygiene during menstruation at SMP Negeri 1 Pematangsiantar in 2023. It is hoped that all health workers at SMP Negeri 1 Pematangsiantar will be more active in holding programs such as counseling on personal hygiene during menstruation for young women, programs -The program aims to increase the knowledge and attitudes of young women regarding personal hygiene measures during menstruation